Prevalence and awareness of text neck syndrome and text thumb syndrome in young adult population - B, Senthil Kumar; Khaleeluddin, Kouser Banu; Jayakumar, Saikarthick; K, Ezhil Vendhan (Creative Pharma Assent, 2024)
Background: The term